Spontaneous Septostomy in a Twin Pregnancy Causing Fatal Amniotic Band Syndrome. (30th December 2018) - Hvelplund, Carolina; Pihl, Kasper; Trautner, Simon; Pedersen, Pernille; Maroun, Lisa Leth
Abstract : Complications due to spontaneous septostomy of the dividing membrane in monochorionic diamniotic pregnancies are rarely described. Herein, we report the case of a preterm female neonate from a monochorionic diamniotic twin pregnancy delivered by caesarean section at 32 weeks of gestation. She was born with a broad band of a transparent membrane-like material firmly attached to her lower abdomen. Postnatally, she developed respiratory distress syndrome and persistent pulmonary hypertension, complicated by bilateral pneumothorax. She died due to respiratory failure when she was 1 day old. Her twin sister survived with no malformations. At postmortem examination, the neonate had severe lung hypoplasia, and the attached material was diagnosed as the dividing septum. We hypothesize that the lung hypoplasia was secondary to local oligohydramnios, which developed as a consequence of the twin being firmly stuck in the defect of the dividing membrane. To our best knowledge, spontaneous septostomy causing an ultimately fatal amniotic band syndrome has not previously been described.